Issue Information TOC. Issue 1 (17th December 2019) - Unknown
Abstract : Cover : In Chong et al. (http://doi.org/10.1002/cpbi.86 ), the image shows the MetaboAnalyst 4.0 flowchart. There are two main components: a data processing component to deal with different data inputs, and a data analysis component containing individual modules which can be categorized into "Exploratory Statistical Analysis, " "Functional Enrichment Analysis, " and "Data Integration and Systems Biology." PROT X refers to the relevant protocol for that component/module.